Three-dimensional graphene-carbon nanotube hybrid for high-performance enzymatic biofuel cells - Chen, Peng (2014)
Enzymatic biofuel cells (EBFCs) are promising renewable and implantable power sources. However, their power output is often limited by inefficient electron transfer between the enzyme molecules and the electrodes, hindered mass transport, low conductivity and small active surface area of the electrodes. To tackle these issues, we herein demonstrated a novel EBFC equipped with enzyme-functionalized 3D graphene – single walled carbon nanotubes (SWCNTs) hybrid electrodes using the naturally abundant glucose as the fuel and oxygen as the oxidizer. Such EBFCs, with high stability, can nearly attain the theoretical limit of open circuit voltage (~1.2 V) and a high power density ever reported (2.27 ± 0.11 mW cm-2).